Wallace Stevens and the limits of reading and writing - Eeckhout, Bart, 1964- (University of Missouri Press, 2002)
"Stevens's work has been interpreted so variously and contradictorily that critics must first address the question of limits to the poetry's signifying potential before they can attempt to deepen our appreciation of it. In the first half of this book, the limits of appropriating and contextualizing Stevens's "The Snow Man," in particular, are investigated. Eeckhout does not undertake this reading with the negative purpose of disputing earlier interpretations but with the more positive intention of identifying the intrinsic qualities of the poetry that have been responsible for the remarkable amount of critical attention it has received." "Stevens's work presents one of the most poignant opportunities for letting the reader feel the ever-problematic relationship between specificity and generality that is at the heart of all literary writing. By negotiating between the particularity of poetic detail and the universality of philosophical ideas, Wallace Stevens and the Limits of Reading and Writing seeks to contribute both to the study of Stevens and to the fields of literary theory and philosophy."--Jacket